2018
DOI: 10.1088/1748-0221/13/02/t02001
|View full text |Cite
|
Sign up to set email alerts
|

Element-specific spectral imaging of multiple contrast agents: a phantom study

Abstract: This work demonstrates the feasibility of simultaneous discrimination of multiple contrast agents based on their element-specific and energy-dependent X-ray attenuation properties using a pre-clinical photon-counting spectral CT. We used a photon-counting based pre-clinical spectral CT scanner with four energy thresholds to measure the X-ray attenuation properties of various concentrations of iodine (9, 18 and 36 mg/ml), gadolinium (2, 4 and 8 mg/ml) and gold (2, 4 and 8 mg/ml) based contrast agents, calcium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
(70 reference statements)
2
17
0
Order By: Relevance
“…Bateman et al [4] also reported similar observations. However, we have not encountered similar problem of Perspex being misidentified with other high-Z elements, such as iodine and gold in one of our earlier studies [40]. The other reason could be around the similarities in the elemental composition that is The spatial accuracy obtained in our study was consistent to that of previously reported studies using similar image acquisition and MD methods [12], [16].…”
Section: Discussionsupporting
confidence: 87%
“…Bateman et al [4] also reported similar observations. However, we have not encountered similar problem of Perspex being misidentified with other high-Z elements, such as iodine and gold in one of our earlier studies [40]. The other reason could be around the similarities in the elemental composition that is The spatial accuracy obtained in our study was consistent to that of previously reported studies using similar image acquisition and MD methods [12], [16].…”
Section: Discussionsupporting
confidence: 87%
“…Lab-based spectral imaging systems incorporating photon-counting energy-resolving detectors are now available. These are able to assign photons to a small number of energy thresholds per pixel and can thus distinguish multiple stains simultaneously [72]. The logical extension of this approach is hyperspectral CT using an energy-sensitive detector to record the full X-ray energy profile at each pixel [73].…”
Section: Obtaining Contrast For Soft Tissue Imaging In Aqueous Conditmentioning
confidence: 99%
“…The enhancement in X-ray attenuation property of A13 nanocomposite is also attributed to the presence of heavy atoms such as Bi and Gd which exhibit a K-absorption edge or K-edge effect (defined as an increase in photoelectric absorption which occurs when the energy of incoming X-ray photons matches with the binding energy of K-shell electrons in an atom) at 90.5 and 50.2 keV X-ray photon energy, respectively. 70,71 The dual K-edge effect observed in A13 nanocomposite greatly enhances its X-ray attenuation property in the diagnostic range. Figure 10(f) shows the radiograph image of polymer-Bi 2 O 3 -Bi nanocomposite (A7), with less number of pin-holes.…”
Section: Resultsmentioning
confidence: 99%